Lower-limb asymmetries in jump athletes during single-leg drop jump - Li, Yunman; Zhang, Xinxin; Zhou, Yong; Sun, Yuliang (Frontiers in Physiology, 2025)
BackgroundThis study investigated lower-limb biomechanical asymmetries during single-leg drop jumps (SLDJ) in elite male long and high jumpers.MethodsTwenty athletes performed SLDJ from 30-cm and 40-cm heights using dominant and non-dominant legs. Three-dimensional kinematic and kinetic data were collected using a motion capture system and force platforms. Measured variables included joint angles, moments, peak vertical ground reaction force (Peak vGRF), loading rate, reactive strength index (RSI), and absolute symmetry index (ASI%). Data were analyzed using a two-way repeated-measures ANOVA.ResultsThe dominant leg exhibited significantly greater ankle range of motion (p < 0.05), hip joint moment (p < 0.05), ankle joint moment (p < 0.001), and peak vGRF (p < 0.001) compared to the non-dominant leg. Furthermore, knee joint moments (p < 0.05) and RSI (p < 0.001) were significantly greater at the 40 cm height than at the 30 cm height. The ASI% for the peak vGRF (30 cm: 10.74% ± 9.24%, 40 cm: 14.87% ± 13.75%) and the loading rate (30 cm: 15.47% ± 14.81%, 40 cm: 20.27% ± 9.80%) exceeded 10%, which indicated asymmetry between the two legs during the single-leg drop jump impact.ConclusionThese findings suggest a trend wherein inter-limb asymmetry during the single-leg drop jump appeared to become more pronounced with increasing drop height. This observation may offer valuable insight for sport-specific performance assessment and targeted injury prevention.